2002
DOI: 10.1002/ajmg.b.10004
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of dopamine receptors and tardive dyskinesia among Chinese patients with schizophrenia

Abstract: The putative role of dopamine in the pathophysiology of tardive dyskinesia (TD) makes the genes coding for dopamine receptors the appropriate candidates for study. We investigate the association of the polymorphism of the Ser311Cys and Ser9Gly of the dopamine D2 (DRD2) and D3 receptor (DRD3) genes respectively with TD in Chinese patients with schizophrenia. In a case-control study, 117 Chinese patients with TD were compared to 200 patients without TD. Patients were diagnosed to have schizophrenia according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
3
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 26 publications
3
33
3
2
Order By: Relevance
“…The Gly variant is reportedly associated with significantly higher dopamine activity, which in turn could explain the association with movement disorders. 238 Only one study reported the Ser/Ser genotype associated with increased risk of TD after correcting for age in a large Chinese cohort, 226 a contradiction that may be explained by different LD status in this population. A recent meta-analyses showed that the D3 Gly9 allele conferred an increased risk of developing TD (P = 0.04, O.R.…”
Section: Prediction Of Side Effectsmentioning
confidence: 96%
See 1 more Smart Citation
“…The Gly variant is reportedly associated with significantly higher dopamine activity, which in turn could explain the association with movement disorders. 238 Only one study reported the Ser/Ser genotype associated with increased risk of TD after correcting for age in a large Chinese cohort, 226 a contradiction that may be explained by different LD status in this population. A recent meta-analyses showed that the D3 Gly9 allele conferred an increased risk of developing TD (P = 0.04, O.R.…”
Section: Prediction Of Side Effectsmentioning
confidence: 96%
“…Only one report suggested association between D2 polymorphisms and TD, 229 but no evidence was found by other groups. 204,[223][224][225][226][227][228] Similarly, no association was found when investigating D1 polymorphisms and a polymorphism in the dopamine transporter (DAT) in relation to TD, 204 and no association was found between D2 and D3 polymorphisms and tardive distonia, an uncommon druginduced movement disorder, in a pilot study on nine patient sufferers. 240 Serotonin inhibition of dopamine function may also contribute to the pathological events related to movement disorders.…”
Section: Prediction Of Side Effectsmentioning
confidence: 99%
“…Early studies did not show an association with Taq1A or other polymorphisms. [56][57][58][59][60][61] One study found a significant association between the Taq1A polymorphism of the dopamine 2 receptor gene (DRD2) and TD in female patients. 62 Another study showed an increased risk for EPS in patients with the À141C Del allele of the DRD2 gene.…”
Section: Dopamine 2 Receptormentioning
confidence: 99%
“…Six included the number of patients with and without TD and genotypes for Taq1A, while five included the number of TD-positive and TD-negative patients with genotypes for the À141C Ins/Del polymorphism. [2][3][4][5][6][7][8] All subjects were selected based on their diagnoses of schizophrenia or schizoaffective disorder, according to DSM-III-R or IV, using case records with or without patient interviews. The presence of TD was assessed from our study using the Abnormal Involuntary Movement Scale (AIMS) or the modified Hillside Simpson Dyskinesia Scale (HSDS) in the case of 49 patients, as described previously.…”
mentioning
confidence: 99%